Attrition and the Gender Patenting Gap - Aneja, Abhay; Reshef, Oren; Subramani, Gauri (The Review of Economics and Statistics, 2026)
Women are underrepresented in patenting. In this study, we consider differential responsiveness to rejection as a contributor to the gender gap in invention. Leveraging the prosecution histories of almost one million U.S. patent applications and the quasirandom assignment of applications to examiners, we show that women are 3.6–6.9 percentage points less likely to continue in the application process following an early-stage rejection. Conditional on applying for a patent, male-female disparities in the propensity to abandon applications account for more than half of the overall gender gap in issued patents. We provide suggestive evidence that institutional support can help reduce the attrition gap.